An Inconstant Landscape : The Maya Kingdom of El Zotz, Guatemala - Houston, Stephen D.; Garrison, Thomas G. (Thomas Gardner) (Book collections on Project MUSE., 2018)
Presenting the results of six years of archaeological survey and excavation in and around the Maya kingdom of El Zotz, An Inconstant Landscape paints a complex picture of a dynamic landscape over the course of almost 2,000 years of occupation. El Zotz was a dynastic seat of the Classic period in Guatemala. Located between the renowned sites of Tikal and El Perú-Waka', it existed as a small kingdom with powerful neighbors and serves today as a test-case of political debility and strength during the height of dynastic struggles among the Classic Maya. In this volume, contributors address the challenges faced by smaller polities on the peripheries of powerful kingdoms and ask how subordination was experienced and independent policy asserted. Leading experts provide cutting-edge analysis in varied topics and detailed discussion of the development of this major site and the region more broadly. The first half of the volume contains a historical narrative of the cultural sequence of El Zotz, tracing the changes in occupation and landscape use across time; the second half provides deep technical analyses of material evidence, including soils, ceramics, stone tools, and bone. The ever-changing, inconstant landscapes of peripheral kingdoms like El Zotz reveal much about their more dominant--and better known--neighbors. An Inconstant Landscape offers a comprehensive, multidisciplinary view of this important but under-studied site, an essential context for the study of the Classic Maya in Guatemala, and a premier reference on the subject of peripheral kingdoms at the height of Maya civilization.